(untitled) (Journal of the College of Basic Education, 2025)
Economic history has been important throughout history, as it represents the lifeblood of peoples and the strength of states. This is evident in the books of legal rulings and jurisprudence. Among the concerns of Judge Iyad in his many books, the legal rulings he mentioned included matters related to crops, sales, property, industry, trade, markets, and the related problems and disputes. These issues give us a clear picture of economic life in Judge Iyad’s era. Through his books, we will trace these economic conditions that Judge Iyad documented during his lifetime.